Binding‐Mediated Formation of Ribonucleoprotein Corona for Efficient Delivery and Control of CRISPR/Cas9. (17th March 2021) - Wu, Jinjun; Peng, Hanyong; Lu, Xiufen; Lai, Maode; Zhang, Hongquan; Le, X. Chris
Abstract: Protein coronae formed with nanoparticles confer several useful properties. However, the non‐specific nature of protein corona formation makes it difficult to deliver specific proteins for therapeutic applications. Herein, we report on the construction of a new type of protein corona, termed binding‐mediated protein corona. This new corona enables the efficient and controllable delivery of functional proteins, which is otherwise challenging for conventional protein coronae. We show the design and delivery of the ribonucleoprotein corona for the CRISPR/Cas9 system. Successful gene editing in human cell lines (Hela and HEK293) demonstrates the efficient delivery, high stability, low cytotoxicity, and well‐controlled activity of the Cas9‐guide RNA ribonucleoprotein. The binding‐mediated protein corona strategy opens up new opportunities for therapeutic protein delivery. Abstract : We report on the construction of a new type of protein corona, termed binding‐mediated protein corona. This new corona enables the efficient and controllable delivery of functional proteins, which is otherwise challenging for conventional protein coronae.